1989
DOI: 10.1016/0735-1097(89)90082-x
|View full text |Cite
|
Sign up to set email alerts
|

Quinidine-induced long qtu interval and torsade de pointes: Role of bradycardia-dependent early afterdepolarizations

Abstract: Right ventricular endocardial monophasic action potential recordings were obtained in a patient with a qunidine-induced long QTU interval and polymorphic ventricular tachycardia of the torsade de pointes type. The recording showed a deflection on phase 3 repolarization characteristic of early afterdepolarization. The early afterdepolarization was synchronous with the U wave in surface electrocardiographic leads and there was a strong correlation between the amplitude of both waves. A strong correlation was als… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
28
0
3

Year Published

1991
1991
2013
2013

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 104 publications
(34 citation statements)
references
References 17 publications
3
28
0
3
Order By: Relevance
“…The arrhythmia may be due to sustained rapid EADs, oscillatory potentials triggering the first EADs, reentry resulting from the electrical heterogeneity caused by the EADs, or some other mechanism. El-Sherif et al28, 29 recently showed that the first ectopic beat arose from the peak of the EADs and the U wave, both in dogs treated with anthopleurin-A and in a case of quinidine-induced torsade de pointes. They suggested that the initiating beats of VTs are due to a triggered rhythm arising from the EADs.30 However, the mechanism of subsequent VT beats is still unclear.…”
Section: Mechanism Of Ventricular Tachyarrhythmiasmentioning
confidence: 99%
“…The arrhythmia may be due to sustained rapid EADs, oscillatory potentials triggering the first EADs, reentry resulting from the electrical heterogeneity caused by the EADs, or some other mechanism. El-Sherif et al28, 29 recently showed that the first ectopic beat arose from the peak of the EADs and the U wave, both in dogs treated with anthopleurin-A and in a case of quinidine-induced torsade de pointes. They suggested that the initiating beats of VTs are due to a triggered rhythm arising from the EADs.30 However, the mechanism of subsequent VT beats is still unclear.…”
Section: Mechanism Of Ventricular Tachyarrhythmiasmentioning
confidence: 99%
“…Furthermore, the onset of torsades de pointes is constantly preceded by a sudden increase in the RR interval with an abnormally prolonged QT interval. 41,50 Therefore, it is likely that LQTS patients are prone to the occurrence of such arrhythmias through an instantaneous greater adaptability of their QT interval to their heart rate. Indeed, LQTS patients have previously been shown to have a greater adaptability of both monophasic APD and QT intervals to their heart rate, at rest and during exercise.…”
Section: Drici Et Al July 13 1998 99mentioning
confidence: 99%
“…The proposed underlying mechanism is the triggering of oscillations known as early afterdepolarizations that interrupt the normal repolarizing time course of the APD, especially at slow heart rates. 49,50 The lack of I Ks may facilitate the occurrence of early afterdepolarizations in 2 ways: (1) by delaying the repolarization phase and lengthening the action potential first, enabling inward currents to reactivate, 51 and (2) by opposing weakened outward conductances on the emergence of such depolarizations. Furthermore, the onset of torsades de pointes is constantly preceded by a sudden increase in the RR interval with an abnormally prolonged QT interval.…”
Section: Drici Et Al July 13 1998 99mentioning
confidence: 99%
“…27 Magnesium suppresses the early afterdepolarizations and ventricular tachyarrhythmias in these animal models32,36 as it suppresses ventricular tachyarrhythmias in patients with the acquired LQTS.37 In addition, deflections consistent with early afterdepolarizations have been recorded from the hearts of patients with the idiopathic LQTS38-40 and a patient with the acquired LQTS. 41 Where does this leave the role of sympathetic stimulation? In the animal model of LQTS produced by cesium chloride administration, bilateral and left ansae subclaviae stimulation produces larger early afterdepolarizations and increases the prevalence of spontaneous ventricular tachyarrhythmias to a greater degree than does right ansae subclaviae stimulation.…”
Section: Intrinsic Abnormality In Repolarizationmentioning
confidence: 99%